Angel of the battlefield - Hood, Ann, 1956- (The Treasure Chest ;, 2012)
When their parents divorce, twelve-year-old twins Felix and Maisie move with their mother to live in the attic of a historic Newport, Rhode Island, mansion where they discover a hidden room that carries with it an intriguing secret.